Detyrosinated tubulin is decreased in fetal vessels of preeclampsia placentas - Huebner, H.; Knoerr, B.; Betzler, A.; Kehl, Sven; Baier, F.; Wachter, David Lukas; Strick, Reiner; Beckmann, Matthias; Fahlbusch, F. B.; Rübner, Matthias; Hartner, Andrea (Placenta, 2018)
INTRODUCTION: Preeclampsia is a hypertensive, gestational disease, which is still the leading cause of pregnancy related morbidity and mortality. The impairment of placental angiogenesis and vascularization is discussed to be of etiopathologic relevance. Deytrosination and tyrosination of α-tubulin is important for the stability and dynamics of microtubules. An increase of α-tubulin detyrosination leads to microtubule stabilization, which is an essential prerequisite for physiologic vascular tube morphogenesis during angiogenesis. So far, little is known about the specific localization of detyrosinated (detyr) and tyrosinated (tyr) tubulin in the placenta and its relevance for preeclampsia. METHODS: Placental expression of detyr- and tyr-tubulin was analyzed by immunohistochemistry, immunofluorescence and western blot. For western blot quantification we used biopsies from healthy placentas (n = 21) and placentas from pregnancies complicated with small for gestational age (n = 5), preeclampsia (n = 5) or both (n = 5). RESULTS: Specific placental localization of detyr-tubulin was detected in the fetal endothelial cells of the placenta. Villous and extravillous trophoblasts as well as villous stroma cells were tyr-tubulin positive. Detyr-tubulin protein expression was significantly decreased in placentas complicated by preeclampsia. CONCLUSIONS: In summary, we report an accumulation of detyr-tubulin in villous vessels of the placenta and a significantly reduced level of detyr-tubulin in placental biopsies of preeclampsia cases. The reduction of placental detyr-tubulin in preeclampsia could suggest a deficit in villous vascular plasticity and might be associated with the impaired arborization of the disease.
EVALuna2:34296